Key Components of Musical Discourse Analysis - Aleshinskaya, Evgeniya (Research in Language, 2013)
Musical discourse analysis is an interdisciplinary study which is incomplete without consideration of relevant social, linguistic, psychological, visual, gestural, ritual, technical, historical and musicological aspects. In the framework of Critical Discourse Analysis, musical discourse can be interpreted as social practice: it refers to specific means of representing specific aspects of the social (musical) sphere. The article introduces a general view of contemporary musical discourse, and analyses genres from the point of ‘semiosis’, ‘social agents’, ‘social relations’, ‘social context’, and ‘text’. These components of musical discourse analysis, in their various aspects and combinations, should help thoroughly examine the context of contemporary musical art, and determine linguistic features specific to different genres of musical discourse.